PENGARUH MEDIA PEMBELAJARAN e-LKPD BERBANTUAN LIVE WORKSHEETS TERHADAP HASIL BELAJAR PESERTA DIDIK - Sri Wulandari; Rahayu Condro Murti; Banu Setyo Adi (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Student learning outcomes tend to be low because the media used has not been able to improve learning outcomes even though in the era of sophisticated technology teachers can use interesting media. So that the solution to this problem, teaching materials must be developed in an interesting way. Live worksheet which contains sheets containing assignments that must be done by students. One of them is technology-based media, namely e-LKPD by live worksheets. This study aims to determine the effect of e-LKPD learning media by live worksheets on student learning outcomes. This research method uses a quantitative approach to the type of Pre-Test and Post-Test. Data collection techniques in this study used a learning outcomes questionnaire. The population used in this study was class III at SDN Girirejo and sample used in this study totaled 28 students. Data analysis using one-sample t-test. Based on the results of the Validity Test, the results showed that r = 0.396> α (0.05) so that all item items showed valid results. Reliability test if the value of α > 0.769 the value is reliable, namely 0.769. The results of the normality test for the value of learning outcomes are 0.185 > α (0.05), then the variable values are normally distributed, followed by using the one-sample t-test, the results of the t-test results are learning outcomes on the t-statistic value of 7,850> α (0.05) then reject H0. So it can be concluded that there is an influence of e-LKPD learning media assisted by live worksheets on student. Keywords: Count numbers, e-LKPD live worksheet, learning outcomes